Thermally stimulated depolarization of dipole rotator in symmetric potential of hindered rotation - Tsyomyk (Vovchenko), O. Ye.; Klymenko, V. E.; Rozenbaum, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
The approximate and exact expressions for the thermally stimulated depolarization current of adsorbed polar molecule in symmetric n-well potential of hindered rotation have been obtained. An analytical relation is derived for estimation of the rotation activation energy from the temperature of spectrum maxima of thermally stimulated depolarization. The maximum value of the current at temperature T=21.5 К is about 10-13 А for the characteristic values of the system of hydroxyl groups on silica surface and the heating rate coefficient; this value is quite sufficient for experimental measurements.